Identifikasi Struktur Ruang dan Persebaran Fasilitas Pelayanan di Kelurahan Kahuripan, Kecamatan Tawang, Kota Tasikmalaya - Stefanny Tri Angelika; Siti Fadjarajani; Cahya Darmawan (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This study aims to identify the spatial structure and distribution of service facilities in Kahuripan Village, Tawang District, Tasikmalaya City. As one of the areas experiencing rapid development, Kahuripan Village has a strategic location that influences spatial dynamics, especially in social and economic aspects. The research method used is descriptive qualitative, with data collection techniques through field surveys, interviews, documentation studies, and literature studies. The results of the study indicate that the spatial structure in Kahuripan Village tends to follow a multiple center pattern, with two main centers functioning as government centers and economic centers. The distribution of service facilities, such as education, health, trade, and worship, is quite even and adequate. A good road network also supports mobility and access to these facilities. The conclusion of this study is that Kahuripan Village has great potential to continue to develop as a new service center, with development directed at micro, small, and medium enterprises (MSMEs), as well as improving accessibility and sustainability of land use in accordance with the Regional Spatial Plan (RTRW).